RNA-seq analysis reveals key genes associated with seed germination of Fritillaria taipaiensis P.Y.Li by cold stratification - Yang, Qiu-Xiong; Chen, Dan; Zhao, Yan; Zhang, Xiao-Yu; Zhao, Min; Peng, Rui; Sun, Nian-Xi; Baldwin, Timothy Charles; Yang, Sheng-Chao; Liang, Yan-Li (Frontiers in Plant Science, 2022)
Seed dormancy is an adaptive strategy for environmental evolution. However, the molecular mechanism of seed dormancy-breaking at cold temperature is not clear, and the germination regulation network initiated by cold temperature needs to be further studied. In this study, the characteristics of seed coat and the growth of embryo at different temperatures were measured. The results showed that the embryo elongation and the dormancy-breaking was significantly affected at 4℃. Transcriptome analyses of seeds from Fritillaria taipaiensis P.Y.Li in different dormant states at two stratification temperatures of 4℃ and 25℃ was performed, combined with weighted gene coexpression network analysis (WGCNA) and metabolomics to explore the transcriptional regulation mechanism of seeds germination of F. taipaiensis at cold temperature. The results showed that cold temperature could up-regulate genes expression involved in gibberellic acid (GA) and auxin pathway and down-regulate genes expression related to abscisic acid (ABA) pathway, promoting the embryo development and stimulating seed germination. Collectively, our findings allow the sketching of a role of cold temperature in the regulation of seeds germination in F. taipaiensis and also provided valuable transcriptomic data for seed dormancy in non-model plants.